Deconstruction of Hifdzun Nasl in Maqasid Syari'ah: Analysis of the Childfree Phenomenon from the Perspective of Islamic Family Law - Khoirul Umam Addzaky; Taufiqurohman; Muhammad Asy'ari (UIN Sunan Kalijaga Yogyakarta, 2025)
This study examines the conceptual transformation of Hifdzun Nasl (protection of offspring) within the Maqasid Sharia framework as a response to the Childfree phenomenon that is increasingly prevalent in contemporary society. Through a deconstructive approach to classical interpretation, this study aims to map the paradigmatic shift of the concept of Hifdzun Nasl from traditional formulation to modern contextualization, and analyze its implications in the reformulation of Islamic family law. The research methodology combines substantive content analysis with comparative literature studies sourced from classical and contemporary ushul fiqh books. The results identify an epistemological limitation in the conventional interpretation of Hifdzun Nasl, which dominantly emphasizes aspects of biological procreation alone. Contemporary reorientation offers a conceptual expansion that includes dimensions of generational quality, ecological sustainability, and non-biological manifestations of offspring. The analysis shows that the reconceptualization of Hifdzun Nasl opens a discursive space for the legitimization of Childfree choices in an Islamic juridical perspective, with significant implications for the reconfiguration of fundamental aspects of marriage law, inheritance, and alternative parenting. This research contributes to the development of Maqasid epistemology that is more inclusive and responsive to contemporary social dynamics, as well as offering a theoretical framework for integrating the phenomenon of Childfree into the discourse of Islamic family law without distorting the fundamental principles of Sharia. These findings emphasize the urgency of a progressive-contextual approach in the interpretation of Maqasid to answer the complexity of family law problems in the modern era